Multiple Disruptions of Glial-Neuronal Networks in Epileptogenesis That Follows Prolonged Febrile Seizures - Brennan, Gary P.; Garcia-Curran, Megan M.; Patterson, Katelin P.; Luo, Renhao; Baram, Tallie Z. (Frontiers in Neurology, 2021)
Two way neuronal-glial communication is a critical mediator of brain function and is measurably disrupted in epilepsy. The role of aberrant glial function during epileptogenesis and the resultant epilepsy is important because the mediators involved provide tangible targets for intervention. Glial activation is intrinsically involved in the generation of febrile seizures (FS), and prolonged FS (febrile status epilepticus, FSE) antecede a proportion of adult temporal lobe epilepsy (TLE). Because TLE is often refractory and accompanied by significant memory difficulties, we probed the role of disruptions of glial-neuronal networks in the epileptogenesis following FSE. We performed a multi-pronged examination of neuronal-glia communication and the resulting signaling cascades following experimental FSE (eFSE) in immature rats. Specifically, we looked at pathways involving cytokines, microRNAs, high mobility group B 1 (HMGB1) and the prostaglandin E2 signaling. We aimed to block epileptogenesis using network-specific interventions as well as via a global anti-inflammatory approach using dexamethasone. A) eFSE elicited a rapid inflammatory response with sustained upregulation of pro-inflammatory cytokines. B) Within minutes of the end of the eFSE, HMGB1 translocated from neuronal nuclei to dendrites, en route to the extracellular space and glial Toll-like receptors. Administration of an HMGB1 blocker to eFSE rat pups did not suppress inflammatory cascades and led to unacceptable side effects. C) Prolonged seizure-like activity, caused overall miRNA-124 levels to plunge in hippocampus, however seizure-like activity promoted its inclusion in exosomes and release. D) Within hours of eFSE, structural astrocyte and microglia activation was associated with activation of the PGE2 cascade. Again, administration of TG6-10-1, a blocker of the PGE2 receptor EP2 had little effect on spike-series provoked by eFSE. E) Remarkably, treatment of eFSE-rats with the broad anti-inflammatory drug dexamethasone attenuated eFSE-provoked pro-epileptogenic changes observed on EEG eFSE, an insult provoking TLE leads to multiple and rapid disruptions of glial-neuronal networks with a likely role in epileptogenesis. The cell-specific and homeostatic interplays among these pathways constitute a serious challenge to effective selective interventions that aim to prevent epilepsy. In contrast, a broad suppressive measure of glial-neuronal dysfunction holds promise for mitigating FSE-induced hyperexcitability and epileptogenesis in experimental models and in humans.